2001
DOI: 10.1086/393867
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of the Attine Ant-Fungus Mutualism

Abstract: Cultivation of fungus for food originated about 45-65 million years ago in the ancestor of fungus-growing ants (Formicidae, tribe Attini), representing an evolutionary transition from the life of a hunter-gatherer of arthropod prey, nectar, and other plant juices, to the life of a farmer subsisting on cultivated fungi. Seven hypotheses have been suggested for the origin of attine fungiculture, each differing with respect to the substrate used by the ancestral attine ants for fungal cultivation. Phylogenetic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
271
1
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 311 publications
(289 citation statements)
references
References 116 publications
6
271
1
11
Order By: Relevance
“…The most highly advanced and complex agricultural systems are found in the leaf-cutting ant genera Atta and Acromyrmex (Weber, 1966;Mueller et al, 2001;Mueller et al, 2005), which evolved 8-12 million years ago (Schultz and Brady, 2008) and are characterized by mainly collecting fresh plant material . Atta and Acromyrmex workers carry freshly cut leaves to the nest where they process this material into substrate for their crop symbiont Leucocoprinus gongylophorus, by chewing it into minute pieces that are mixed with ''saliva''.…”
Section: Introductionmentioning
confidence: 99%
“…The most highly advanced and complex agricultural systems are found in the leaf-cutting ant genera Atta and Acromyrmex (Weber, 1966;Mueller et al, 2001;Mueller et al, 2005), which evolved 8-12 million years ago (Schultz and Brady, 2008) and are characterized by mainly collecting fresh plant material . Atta and Acromyrmex workers carry freshly cut leaves to the nest where they process this material into substrate for their crop symbiont Leucocoprinus gongylophorus, by chewing it into minute pieces that are mixed with ''saliva''.…”
Section: Introductionmentioning
confidence: 99%
“…However, empirical work over the past two decades has shown that cultivars are frequently transmitted horizontally between different ant colonies (sometimes between colonies of different ant species) and that lower-attine cultivars are closely related to, and in some cases identical to, free-living fungal species, suggesting frequent import of fungi into the symbiosis from free-living sources [12][13][14]17,21,23,[25][26][27][28][29] . This apparent absence of one-to-one host fidelity (that is, long-term association of ant and fungal genotypes), combined with the recent discovery that the lower-attine fungal Clade 2 ( Fig.…”
mentioning
confidence: 99%
“…Moreover, it showed the formation of two distinct groups (Ah and AA) determined by the ant species independently of the geographical region studied. Agreeing with the results, other studies also claimed that different strains of leaf-cutting ants can cultivate in their nests the same symbiotic fungus (MUELLER, 2001;MIKhEYEV et al, 2007). On the other hand, DOhERTY et al (2003) using the RAPD (Random amplified polymorphic DNA) observed genetic variability in isolates originated from symbiotic fungus of Atta cephalotes from Panama and Trinidad.…”
Section: Discussionmentioning
confidence: 66%
“…The genera Atta and Acromyrmex stands out due to the damage they cause, both in native plants and at cultivated plants, in which they cut fresh material that serves as a substrate for the cultivation of the symbiotic fungus inside their nests (ChAPELLA et al, 1994;MUELLER et al, 2001). All Attine ants (that includes about 256 described species in 15 genera) (SOSA-CALVO et al, 2013) are mandatory dependent on this symbiosis, which involves Lepiotaceaeous fungi (order Agaricales, Basidiomycota division) (ChAPELA et al, 1994).…”
Section: Formigas-cortadeiras Dos Gênerosmentioning
confidence: 99%
See 1 more Smart Citation